Is Edema at the Posterior Medial Tibial Plateau Indicative of Ramp Lesion? An Examination of 852 Patients with Anterior Cruciate Ligament Reconstruction. Issue 7 (30th July 2018) - Kumar, Neil; Spencer, Tiahna; Hochman, Edward; Cote, Mark P.; Arciero, Robert A.; Edgar, Cory M.
Objectives: Meniscal injuries are commonly observed with anterior cruciate ligament (ACL) deficiency. A subset of these injuries includes tears of the medial meniscus at the posterior meniscocapsular junction, or ramp lesions. Biomechanical studies have indicated that ramp injuries may compromise anterior stability of the knee, even after ACL reconstruction (ACLR). These lesions are not consistently diagnosed with magnetic resonance imaging (MRI). One criterion that shows promise is the presence of posterior medial tibial plateau (PMTP) edema. A correlation of PMTP edema and peripheral posterior horn medial meniscal injuries has been observed in the literature. We evaluated a consecutive series of patients who underwent ACLR for incidence of ramp tears. These patients were then compared to patients with non-ramp (meniscal body) medial meniscal tears. The utility of PMTP edema on preoperative MRI for ramp tear diagnosis was then determined. Methods: A retrospective chart review via an institutional database search identified 892 patients who underwent ACLR by one of two senior authors (R.A.A., C.E.) between January 2006 and June 2016. Operative notes identified patients diagnosed arthroscopically with medial meniscal lesions, including ramp lesions. Arthroscopic identification was the gold standard for diagnosis of both ramp and non-ramp (meniscal body) tears. Demographic information such as age, sex, laterality, mechanism of injury (contact/noncontact), sport, revision procedure, multi-ligament procedure, time to MRI, and time to surgery were recorded. Patients without available operative records were excluded. Preoperative MRIs were obtained for all patients and reviewed by an orthopaedic sports medicine fellow for PMTP edema. Axial, coronal, and sagittal T2 and proton-density sequences were utilized. A MRI was considered positive if edema was detected in 2 different planes of sequences. Differences between groups were analyzed with two-sample t test or Chi square test Univariate and multivariate logistic regression models analyzed the relationships among patient factors, MRI findings, and ramp lesions. Results: 852 patients met the inclusion criteria for analysis. 307 patients were diagnosed with medial meniscal tear at the time of ACLR, 127 of which were ramp lesions. The overall incidence of ramp tear was 14.9% and consisted of 41.4% of all medial meniscal tears. Patients with ramp tears were mean 7.5 years younger than patients with meniscal body tears ( p <0.01). There was no difference between the groups in regard to mechanism of injury, revision surgery, or multi-ligamentous injury. Patients with delayed ACLR were at 3.3x greater odds ( p <0.01) of having meniscal body tear compared to ramp lesion. MRI was available for review in 178 patients, 97 of whom had positive MRI for PMTP edema. Sensitivity and specificity of PMTP edema for ramp tear was 66.3% and 55.1%, respectively. Of patients with PMTP edema, 54.6% had ramp lesions and 45.4% had non-ramp tears ( p <0.01). Patients with preoperative MRI positive for PMTP edema were at 2.1 times greater odds ( p <0.01) of having sustained a ramp tear compared to a meniscal body tear. Conclusion: The incidence of ramp tear was 14.9% and was more prevalent in younger patients. Delayed ACLR resulted in 3.3x greater odds of meniscal body tears compared to ramp tears. Patients with PMTP edema on preoperative MRI were at 2.1x greater odds to have ramp lesions compared to a meniscal body tears at the time of ACL reconstruction.